Coating liquid, porous film, and lithium ion battery

The use of a coating liquid with inorganic particles and alkali silicate enhances the mechanical strength and heat resistance of battery separators, addressing safety concerns in high-capacity lithium-ion batteries.

JP2025010218AActive Publication Date: 2025-01-20THE JAPAN STEEL WORKS LTD +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2024188310
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2020-10-14
Filing Date
2024-10-25
Publication Date
2025-01-20
Estimated Expiration
2041-08-04

AI Technical Summary

Technical Problem

As lithium-ion batteries increase in capacity and output, there is a need for improved safety features, particularly in the mechanical strength and heat resistance of battery separators to prevent short circuits and enhance shutdown functionality during overheating.

Method used

A coating liquid for porous films used in battery separators is formulated with inorganic particles and alkali silicate, which includes a coating film containing these components to enhance the mechanical strength and heat resistance of the separator, while maintaining battery characteristics.

Benefits of technology

The coating liquid improves the mechanical strength, heat resistance, and electrical characteristics of the porous film and lithium-ion batteries, ensuring better safety and performance under various conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025010218000001_ABST
    Figure 2025010218000001_ABST
Patent Text Reader

Abstract

To improve a characteristic of a porous film used for a separator of a lithium ion battery.SOLUTION: A porous film (a separator) of the present invention, is a porous film having a porous base material S and a coating film CF provided to a front surface of the porous base material. The coating film includes an alkali silicate and a first filler. The first filler is formed by an inorganic particle, and contains 0.05 weight% or more of the alkali silicate to the inorganic particle. The inorganic particle contains a material selected from nano-silica, micro-silica, carbon nano-tube, talc, alumina, boehmite, an aluminum hydroxide, and a glass fiber, and includes a second filler (a hydrophilic group of cellulose is replaced to a hydrophobic group) of 0.05 weight% or more to the inorganic particle. By using the porous film, a battery characteristic such as a heat resistance, a cycle characteristic or the like can be improved.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a coating liquid for a porous film used for battery separators and the like, and can be used for a coating liquid, a porous film, and a lithium ion battery. [Background technology]

[0002] The fields in which secondary batteries are used are expanding from electronic devices to automobiles and large-scale power storage systems, and among them, lithium-ion batteries (secondary batteries) are attracting attention because they can be made small and lightweight and have high energy density.

[0003] For example, Patent Document 1 discloses a non-aqueous binder for electrodes of lithium ion batteries that is a composite of cellulose nanofibers and thermoplastic fluorine-based resin, in which the cellulose nanofibers are cellulose having a fiber diameter of 0.002 μm or more and 1 μm or less, a fiber length of 0.5 μm or more and 10 mm or less, and an aspect ratio (fiber length of cellulose nanofiber / fiber diameter of cellulose nanofiber) of 2 or more and 100,000 or less. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] International Publication No. 2019 / 064583 Summary of the Invention [Problem to be solved by the invention]

[0005] As the capacity and power output of lithium-ion batteries increase, there is a demand for further improvements in safety. The present inventor is engaged in research and development of porous films used for battery separators, etc., and is making intensive studies on porous films with good properties.

[0006] As will be explained in detail later, the separator provided between the positive and negative electrodes of the battery has multiple micropores large enough for lithium ions to pass through, and the lithium ions move between the positive and negative electrodes through these pores, allowing repeated charging and discharging. This separator separates the positive and negative electrodes to prevent short circuits. In addition, if the temperature inside the battery becomes too high for some reason, the micropores in the separator close, stopping the movement of lithium ions and shutting down the battery function (shutdown function).

[0007] In this way, the separator serves as a safety device for the battery, and in order to improve safety, it is essential to improve the mechanical strength and heat resistance of the separator.

[0008] Therefore, it is desirable to investigate a technique for improving the mechanical strength and heat resistance of the separator while maintaining the battery characteristics.

[0009] Other objects and novel features will become apparent from the description of this specification and the accompanying drawings. [Means for solving the problem]

[0010] The coating liquid for a porous film disclosed in one embodiment of the present application contains inorganic particles and 0.05% by weight or more of an alkali silicate relative to the inorganic particles.

[0011] The porous film disclosed in one embodiment of the present application has a porous substrate and a coating film provided on the surface of the porous substrate, and the coating film contains inorganic particles and at least 0.05% by weight of an alkali silicate relative to the inorganic particles.

[0012] A lithium ion battery disclosed in one embodiment of the present application is a lithium ion battery including a positive electrode, a negative electrode, a separator, and an electrolyte, and has the above-mentioned porous film as the separator. Effect of the Invention

[0013] According to the coating liquid for a porous film disclosed in one embodiment of the present application, the properties of the porous film can be improved.

[0014] According to the porous film disclosed in one embodiment of the present application, the properties of the porous film can be improved.

[0015] According to the lithium ion battery disclosed in one embodiment of the present application, the characteristics of the lithium ion battery can be improved. [Brief description of the drawings]

[0016] [Figure 1] 1 is a cross-sectional view showing a configuration of a porous film according to a first embodiment. [Diagram 2] FIG. 2 is a diagram showing a schematic internal configuration of a lithium ion battery using the porous film of the first embodiment. [Diagram 3] FIG. 1 is a diagram illustrating a configuration example of a lithium ion battery according to a first embodiment. [Figure 4] FIG. 1 is a diagram showing the steps for preparing a dispersion of hydrophobized cellulose nanofibers (CeNFs). [Diagram 5] FIG. 1 shows the hydrophobization of cellulose. [Figure 6] FIG. 2 is a perspective view showing a coating step of a coating liquid using a bar coater. [Figure 7] FIG. 1 is a diagram showing the results of heat shrinkage test 1. [Figure 8] FIG. 1 is a diagram showing the results of heat shrinkage test 1. [Figure 9] FIG. 1 is a diagram showing the results of heat shrinkage test 1. [Figure 10] FIG. 1 is a diagram showing the results of heat shrinkage test 1. [Figure 11] FIG. 13 is a diagram showing the results of heat shrinkage test 2. [Figure 12] FIG. 1 shows the results of SEM observation. [Figure 13] FIG. 1 shows the results of SEM observation. [Figure 14] FIG. 1 shows the results of SEM observation. [Figure 15] FIG. 1 shows the results of SEM observation. [Figure 16] FIG. 1 shows the results of SEM observation. [Figure 17] FIG. 1 shows the results of SEM observation. [Figure 18] 1 is a graph showing the results of a puncture test of porous films (separators) 1, 2, and A. [Figure 19] 1 is a graph showing the Gurley values ​​of porous films (separators) 1, 2, and A. [Figure 20] FIG. 1 shows cycle characteristics at 30° C. [Figure 21] FIG. 1 is a graph showing cycle characteristics at 60° C. [Figure 22] 1 is a diagram (graph) showing the battery resistances of batteries 1, 2, A, and B. [Diagram 23] FIG. 13 is a diagram showing the results of heat shrinkage test 2. [Figure 24] FIG. 1 shows cycle characteristics at 30° C. [Diagram 25] FIG. 1 is a graph showing cycle characteristics at 60° C. [Figure 26] 13 is a diagram (graph) showing the battery resistances of batteries 3 and B. [Figure 27] FIG. 11 is a schematic diagram showing the configuration of a manufacturing apparatus according to a third embodiment. [Figure 28] FIG. 2 is a cross-sectional view showing a schematic configuration of a gravure coating device. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] Hereinafter, the embodiment will be described in detail with reference to examples and drawings. In all the drawings for explaining the embodiment, the same reference numerals are used to designate members having the same functions, and the repeated description thereof will be omitted.

[0018] (Embodiment 1) The porous film of the present embodiment and the method for producing the same will be described below. The porous film of the present embodiment can be used as a so-called battery separator.

[0019] [Structure description] Fig. 1 is a cross-sectional view showing the structure of a porous film of the present embodiment. As shown in Fig. 1, the porous film of the present embodiment is used as a separator SP of a battery, and has a substrate (porous substrate) S and a coating film (coating film) CF formed on the surface of the substrate S. As described later, the coating film CF has inorganic particles as a first filler, cellulose subjected to SA treatment (sometimes referred to as SA-Ce or SACE) as a second filler, and an alkali silicate.

[0020] Fig. 2 is a diagram showing a schematic internal structure of a lithium ion battery using the porous film of the present embodiment, and Fig. 3 is a diagram showing a schematic configuration example of the lithium ion battery of the present embodiment. Fig. 2(A) shows the configuration of the positive electrode, Fig. 2(B) shows the configuration of the negative electrode, and Fig. 2(C) shows the configuration of the electrode group. The battery of Fig. 3 is called a coin battery.

[0021] As shown in FIG. 2(A), the positive electrode 1 is composed of a current collector 1S and a positive electrode mixture layer 1M provided thereon, and as shown in FIG. 2(B), the negative electrode 2 is composed of a current collector 2S and a negative electrode mixture layer 2M provided thereon. As shown in FIG. 2(C), the lithium ion battery has a positive electrode 1, a negative electrode 2, and a separator SP disposed therebetween, and the positive electrode 1 and the negative electrode 2 are disposed opposite each other so that the positive electrode mixture layer 1M and the negative electrode mixture layer 2M are in contact with the separator SP, respectively. The laminate (also called an electrode group) of the positive electrode 1, the negative electrode 2, and the separator SP is accommodated in a battery container (a bag made of a laminate film, a battery can, etc.) together with an electrolyte, and is sealed in a state in which the positive electrode terminal (for example, a part of the current collector 1S or a conductive part electrically connected to the current collector 1S) and the negative electrode terminal (for example, a part of the current collector 2S or a conductive part electrically connected to the current collector 2S) are exposed.

[0022] The battery (coin battery) shown in FIG. 3 has a can 6, and the can 6 contains an electrode group in which the positive electrode 1 and the negative electrode 2 are stacked with a separator SP between them. The current collector 1S of the positive electrode 1 on the lower end surface of the electrode group is mounted on the can (battery can) 6. The current collector 2S of the negative electrode 2 on the upper end surface of the electrode group is disposed on the back side of the lid (battery cap) 7. Here, a washer 8 is provided between the lid (battery cap) 7 and the current collector 2S of the negative electrode 2, and they are electrically connected. In addition, a heat-resistant gasket (fixing seal material) is provided at the overlapping portion between the can 6 and the lid 7, and an electrolyte (not shown) injected inside the can 6 is sealed. Here, a coin-type battery has been described, but there is no limitation on the configuration of the battery, and it may be, for example, a cylindrical battery or a laminated battery.

[0023] Thus, the lithium ion battery has a positive electrode 1, a negative electrode 2, a separator SP, and an electrolyte, and the separator SP is disposed between the positive electrode 1 and the negative electrode 2. The separator SP has many micropores. For example, during charging, that is, when a charger is connected between the positive electrode (bottom of the can 6) and the negative electrode (top of the lid 7), the lithium ions inserted in the positive electrode active material are desorbed and released into the electrolyte. The lithium ions released into the electrolyte move through the electrolyte and pass through the micropores of the separator to reach the negative electrode. The lithium ions that reach the negative electrode are inserted into the negative electrode active material that constitutes the negative electrode.

[0024] In this manner, lithium ions move between the positive electrode and the negative electrode via the micropores (not shown) provided in the substrate S shown in FIG. 1, thereby enabling repeated charging and discharging.

[0025] Here, in the porous film of the present embodiment, as shown in Fig. 1, a coating film CF is provided on the surface of a substrate S having a large number of micropores. This coating film CF has inorganic particles as a first filler, and cellulose that has been subjected to SA treatment (sometimes referred to as SA-Ce) and an alkali silicate as a second filler. The SA treatment is a treatment that makes some of the hydrophilic groups of cellulose hydrophobic.

[0026] Thus, in this embodiment, the mechanical strength and heat resistance of the porous film (separator) can be improved by providing the coating film on the surface of the substrate S. The coating film CF is not formed so as to cover all of the micropores of the substrate S, and the Gurley value (air permeability, [sec / 100cc]) of the substrate S (porous film, separator) on which the coating film CF is formed is 200 or more and 3000 or less, ensuring air permeability.

[0027] In particular, by adding an alkali silicate to the coating liquid, it is possible to improve the electrical characteristics (output characteristics, cycle characteristics (life)) of the battery while improving the mechanical strength and heat resistance of the porous film (separator).

[0028] [Production method description] The manufacturing process of the porous film of this embodiment will be described below, and the configurations of the porous film and the coating film will be made clearer.

[0029] The manufacturing process of the porous film of the present embodiment includes the following steps.

[0030] <<1: Preparation process of the substrate (porous film before coating)>> The substrate S can be any substrate without particular limitation, and is preferably a substrate typically used for a porous film for a lithium ion battery, and may be a microporous membrane. For example, a commercially available polyethylene microporous membrane may be used.

[0031] <<2: Coating fluid preparation process>> 2-1) Preparation of the first filler In the present embodiment, inorganic particles (inorganic filler) are used as the first filler.

[0032] The inorganic particles are not particularly limited. For example, alumina, boehmite, aluminum hydroxide, nanosilica, microsilica, carbon nanotubes, talc, glass fiber, etc. can be used. In particular, it is preferable to use alumina from the viewpoint of the stability of physical properties and manufacturing technology and the like, as well as the resistance to chemical reaction with the electrolyte. There is no limitation on the shape of the alumina particles, and for example, spherical or flat shapes can be used. The average particle size (diameter) of alumina is preferably 500 nm or more and 1000 nm or less. The average particle size can be determined by a laser diffraction scattering method. Alumina particles having different average particle sizes may be mixed. Alumina with high purity is used, and even if impurity elements (for example, Si, Fe, Na, Mg, Cu) are contained, it is preferable that Si is 400 ppm or less, Fe is 300 ppm or less, Na is 200 ppm or less, Mg is 100 ppm or less, and Cu is 100 ppm or less.

[0033] 2-2) Preparation of the second filler In the present embodiment, hydrophobized (SA) cellulose (sometimes referred to as SA Ce) is used as the second filler.

[0034] (Hydrophobization) Cellulose (Cellulose, Cell-OH, Ce) is (C 12 H 20 O 10 ) n For example, it can be represented by the following chemical structural formula (Chemical Formula 1): In this chemical structural formula, n, which indicates the average number of repetitions, is a number of 1 or more, preferably 10 to 10,000, and more preferably 50 to 2,000.

[0035] [ka] As shown in the following chemical structure (Chemical Formula 2), (C 12 H 20 O 10 ) nAlternatively, cellulose in which some of the hydroxyl groups of a carbohydrate represented by the formula (I) have been substituted with a group having a hydroxyl group (for example, -R-OH (R represents a divalent hydrocarbon group) such as -CHOH) may be used.

[0036] [ka] As can be seen from the above chemical structural formulas (Chemical Formula 1 and Chemical Formula 2), cellulose has hydroxyl groups (hydrophilic groups). This is hydrophobized (lipophilized) using a hydrophobizing agent (e.g., a carboxylic acid compound). That is, the hydroxyl groups (-OH) of cellulose are replaced with hydrophobic groups. Specifically, some of the hydroxyl groups of cellulose are esterified with a carboxylic acid compound (R-CO-OH). In other words, the hydroxyl groups (-OH) of cellulose are made into ester bonds (-O-CO-R, carboxyl groups). It is not necessary for all of the hydroxyl groups of cellulose to be replaced with hydrophobic groups, as long as some of them are replaced. An example of a cellulose esterification (hydrophobization) reaction is shown in the following reaction formula. Hydrophobized cellulose may be referred to as SA-Ce.

[0037] [ka] The hydrophobizing agent is not particularly limited as long as it has a composition capable of imparting hydrophobic groups to the hydrophilic groups of cellulose, and for example, a carboxylic acid compound can be used. Among them, it is preferable to use a compound having two or more carboxyl groups, an acid anhydride of a compound having two or more carboxyl groups, etc. Among the compounds having two or more carboxyl groups, it is preferable to use a compound having two carboxyl groups (dicarboxylic acid compound).

[0038] Examples of compounds having two carboxy groups include dicarboxylic acid compounds such as propanedioic acid (malonic acid), butanedioic acid (succinic acid), pentanedioic acid (glutaric acid), hexanedioic acid (adipic acid), 2-methylpropanedioic acid, 2-methylbutanedioic acid, 2-methylpentanedioic acid, 1,2-cyclohexanedicarboxylic acid, 2-butenedioic acid (maleic acid, fumaric acid), 2-pentenedioic acid, 2,4-hexadienedioic acid, 2-methyl-2-butenedioic acid, 2-methyl-2-pentenedioic acid, 2-methylidenebutanedioic acid (itaconic acid), benzene-1,2-dicarboxylic acid (phthalic acid), benzene-1,3-dicarboxylic acid (isophthalic acid), benzene-1,4-dicarboxylic acid (terephthalic acid), and ethanedioic acid (oxalic acid). Examples of the acid anhydride of a compound having two carboxy groups include dicarboxylic acid compounds such as maleic anhydride, succinic anhydride, phthalic anhydride, glutaric anhydride, adipic anhydride, itaconic anhydride, pyromellitic anhydride, and 1,2-cyclohexanedicarboxylic anhydride, and acid anhydrides of compounds containing multiple carboxy groups. Examples of the derivatives of the acid anhydride of a compound having two carboxy groups include those in which at least a part of the hydrogen atoms of the acid anhydride of a compound having a carboxy group is replaced with a substituent (e.g., an alkyl group, a phenyl group, etc.), such as dimethylmaleic anhydride, diethylmaleic anhydride, and diphenylmaleic anhydride. Among these, maleic anhydride, succinic anhydride, and phthalic anhydride are preferred because they are easily industrially applicable and easily gasified.

[0039] (Defibrillation process) Cellulose may also be refined (nanofiberized) by defibration. Defibration (refining) can be done by chemical or mechanical methods. A combination of these methods may also be used. This type of defibration (refining) can produce cellulose with a fiber length (L) of 3 nm or more and 10 μm or less, and an aspect ratio (length L / diameter D) of 0.01 or more and 5000 or less. Cellulose fibers refined to nanometer sizes in this way are called cellulose nanofibers (CeNF).

[0040] The above-mentioned pulverization (nanofiberization) of cellulose may be carried out before or after the hydrophobization treatment.

[0041] (Method for preparing hydrophobic CeNF dispersed in a solvent) The hydrophobized CeNF is preferably used in a state dispersed in a solvent in order to prevent aggregation and to improve dispersibility in the coating liquid.

[0042] Fig. 4 is a diagram showing the preparation process of a dispersion liquid of hydrophobized CeNF. For example, as shown in Fig. 4, cellulose (solid, for example, powder) and succinic anhydride (solid, for example, tablet form) are mixed at 100°C or higher. For example, they are mixed for 20 minutes at 125°C using a pressure kneader. The weights of cellulose and succinic anhydride are, for example, 90wt% (weight%, mass%) and 10wt%.

[0043] The mixture is stirred under heating as described above, and an ester reaction occurs to produce hydrophobic cellulose. After this, the mixture is washed with acetone or the like to remove unreacted succinic anhydride.

[0044] Next, the produced hydrophobized cellulose is dispersed in an aqueous solvent (water and / or alcohols, etc., here water (H2O)).

[0045] Fig. 5 is a diagram showing hydrophobization of cellulose (hydrophobized Ce). As shown in Fig. 5, the hydrophobization replaces the hydroxyl groups (-OH) of cellulose with hydrophobic groups (-COOH).

[0046] FIG. 5 shows that eight of the ten hydroxyl groups (-OH) in cellulose have been replaced with hydrophobic groups (-COOH).

[0047] Here, the amount of hydrophobic groups (-COOH) in SA-Ce can be calculated from the acid value. The acid value refers to the number of milligrams of potassium hydroxide required to neutralize the acidic components contained in 1 g of sample, and its measurement can be performed based on "JIS-K0070 Test methods for acid value, saponification value, ester value, iodine value, hydroxyl value and unsaponifiable matter of chemical products." For example, SA-Ce with an acid value of 76.5 mg / g (KOH, formula weight 56.11) has a hydrophobic group (-COOH) content of 1.36 x 10 -3 mol of hydrophobic groups (-COOH).

[0048] Next, a micronization process (fibrillation process, nanoization) is performed. For example, a process using a micronization device (mass colloider, bead mill) is performed to nanonize the cellulose in the dispersion of SA-Ce. This makes it possible to obtain a dispersion of SA-CeNF.

[0049] As described above, the cellulose that has been subjected to the hydrophobic treatment may be subjected to a defibration treatment (fine-refining treatment), or the cellulose may be subjected to the defibration treatment (fine-refining treatment) and then the hydrophobic treatment.

[0050] 2-3) Preparation of alkali silicate As the alkali silicate, it is preferable to use water glass. Water glass is an aqueous solution of silicate of an alkali metal or an alkaline earth metal. For example, in addition to sodium silicate (sodium silicate, Na2O·nSiO2 (n=2-4)), silicates containing Li, K, Rb, Ba, Ca, Mg, Sr, etc. instead of Na can be used, and one type may be used alone, or two or more types may be used in combination.

[0051] Sodium silicate (Na2O·nSiO2 (n=1~5)) can be formed by the thermal reaction of diatomaceous earth with caustic soda, or by dissolving the heated molten material of silica sand and soda ash in water, and there are many inexpensive commercial products available. By adding such water glass, the amount of alumina added can be reduced, for example, to 90wt% or less of the total amount of solid components in the coating liquid, which can reduce costs.

[0052] n, which means the number of SiO2, is preferably 1 to 5, since binding is poor when it is less than 1 or exceeds 5. From the viewpoint of particularly high binding, n is preferably 2 to 4. If the binding is insufficient, peeling and cracking are likely to occur due to external factors such as volume changes of the electrode during charging and discharging and nail penetration tests.

[0053] Among the above alkali silicates, sodium silicate and potassium silicate are particularly excellent in binding, so that the amount of the total solid components of the coating liquid can be 80 wt% or less. On the other hand, lithium silicate is not sufficient in binding compared to sodium silicate and potassium silicate, but it can obtain a battery with low resistance. From the viewpoint of excellent binding and low resistance, it is preferable to use a mixture of sodium silicate or potassium silicate and lithium silicate. If binding is important, the amount of sodium silicate or potassium silicate should be large, and if low resistance is important, the amount of lithium silicate should be large.

[0054] 2-4) Preparation of other additives Other additives that may be added include thickeners (e.g., carboxymethylcellulose, xanthan gum, guar gum, alginic acid), binders (e.g., acrylic resins, acrylic binders, fluororesins), and dispersants (e.g., surfactants, alcohols).

[0055] Carboxymethylcellulose is a water-soluble cellulose salt, and adding it to a coating liquid increases the viscosity and improves the coatability. In addition, adding an acrylic resin improves the adhesiveness of the material in the coating liquid. Specific water-soluble cellulose salts include carboxymethylcellulose-lithium, carboxymethylcellulose-sodium, carboxymethylcellulose-potassium, and carboxymethylcellulose-ammonium. In this application, when carboxymethylcellulose (CMC) is simply mentioned, it means carboxymethylcellulose-sodium.

[0056] The addition of a dispersing agent (surfactant, alcohols) improves wettability to the substrate S. In particular, when using a substrate made of polyethylene or polypropylene, the free energy is large and it is preferable to add a surfactant. The amount of surfactant added is preferably 0.001 wt% or more and 5 wt% or less of the solid components of the coating liquid. There are various types of surfactants, such as anionic surfactants, cationic surfactants, amphoteric surfactants, and nonionic surfactants, and although any of them can be used, nonionic surfactants are preferred because they cause less foaming.

[0057] Here, the solid components of the coating liquid mentioned above refer to the total amount of the SA-CeNF (second filler), inorganic particles (first filler), thickener, binder, and dispersant contained in the coating liquid.

[0058] B) Mixing process (stirring process) A coating liquid is prepared by adding inorganic particles (first filler) and other additives to the above-mentioned dispersion of SA-CeNF (second filler), further adding an alkali silicate, and stirring.

[0059] The amount of SA-CeNF (second filler) added is not particularly limited, but from the viewpoints of coatability, cost, and battery performance, it is preferable to add 0.05 wt% or more to the inorganic particles (first filler). The amount of SA-CeNF added is preferably 0.2 wt% or more and 10 wt% or less, and more preferably 0.5 wt% or more and 5 wt% or less, based on the total amount of solid components in the coating liquid.

[0060] The amount of alkali silicate added is not particularly limited, but from the viewpoints of coatability, cost, and battery performance, it is preferable to add 0.05 wt% or more to the inorganic particles (first filler). Also, the amount of alkali silicate added is preferably 0.3 wt% or more and 20 wt% or less based on the total amount of solid components of the coating liquid, and more preferably 0.5 wt% or more and 15 wt% or less based on the viewpoints of coatability, cost, and battery performance.

[0061] Examples of the stirring method that can be used include a method of rotating a blade attached to a shaft by a motor or the like, a vibration method using ultrasonic waves, etc. In order to reduce the entrapment of air bubbles in the coating liquid, the preparation (mixing, stirring) of the coating liquid may be performed under reduced pressure.

[0062] In addition, a defoaming agent may be added to the coating liquid. When a defoaming agent is added, the amount is preferably 0.001 wt% or more and 1 wt% or less based on the total amount of solid components in the coating liquid. By adding a defoaming agent, air bubbles can be preferably suppressed, and the defoaming step can be simplified or eliminated.

[0063] As the defoaming agent, known agents such as silicone-based defoaming agents (e.g., polydimethylsiloxane), surfactant-based defoaming agents (e.g., polyethylene glycol fatty acid), and alcohols (e.g., acetylene diol) can be used, and among these, silicone-based defoaming agents are preferred from the viewpoint of less adverse effects on the battery. The form of the defoaming agent is not particularly limited, and any type such as oil type, compound type, emulsion type, or powder type can be used.

[0064] <<3: Coating process onto substrate>> The coating liquid is applied to the surface of the substrate S described in <<1: Preparation step of substrate (porous film before coating)>>. There is no limitation on the coating method, but for example, a bar coater, lip coater, gravure coater, die coater, spray coater, screen coater, etc. can be used. After coating, the coating liquid is dried to form a coating film on the surface of the substrate S.

[0065] The drying of the coating liquid is not particularly limited as long as the method can remove the solvent or dispersion medium contained in the coating liquid, and for example, a method of performing heat treatment at a temperature of 50°C or higher and 250°C or lower can be mentioned. The above heat treatment can be performed by holding for 0.1 to 50 hours. The drying environment can be exemplified by air atmosphere, vacuum atmosphere, rare gas atmosphere, nitrogen atmosphere, carbon dioxide atmosphere, and hydrogen atmosphere, and when the environment contains carbon dioxide, the alkali silicate reacts with carbon dioxide to generate a carbonate compound (A2CO3) or a hydrogen carbonate compound (AHCO3) (A = at least one element selected from Li, K, Rb, Ba, Ca, Mg, and Sr). Therefore, when the environment contains carbon dioxide, the alkali silicate contained in the coating film can contain a carbonate compound (A2CO3) or a hydrogen carbonate compound (AHCO3) (A = at least one element selected from Li, K, Rb, Ba, Ca, Mg, and Sr).

[0066] A2CO3 or AHCO3 has the characteristic that it has low solubility in water and decomposes to release carbon dioxide at a voltage exceeding 4.6 V. In other words, by including A2CO3 or AHCO3 in the coating film, the coating film becomes less likely to absorb moisture and can be endowed with the function of releasing carbon dioxide when overcharged.

[0067] The content of A2CO3 or AHCO3 in the coating film is preferably 1 wt% or more and 50 wt% or less. To adjust the content within this range, depending on the heat treatment temperature and heat treatment time, the environmental pressure should be 0.001 to 100 MPa absolute pressure and the carbon dioxide concentration should be 400 ppm or more. More preferably, the environmental pressure is 0.01 to 50 MPa, the carbon dioxide concentration is 1000 ppm or more, and even more preferably, the environmental pressure is 0.1 to 10 MPa, and the carbon dioxide concentration is 2000 ppm or more.

[0068] In addition, by using an alkali silicate in which A2CO3 or AHCO3 powder has been mixed in advance in the coating liquid, the process of heat treatment in an environment containing carbon dioxide can be eliminated, but it is preferable to have the alkali silicate absorb carbon dioxide to generate A2CO3 or AHCO3, because this can greatly reduce the hygroscopicity of the coating film. If the coating film is highly hygroscopic, it may absorb moisture from the air and degrade the battery characteristics.

[0069] When cellulose is included as a second filler in the coating liquid, A2CO3 or AHCO3 can be generated uniformly. In particular, uniformity is improved with cellulose in which hydrophilic groups have been replaced with hydrophobic groups, or with oxidized cellulose in which primary hydroxyl groups have been oxidized to carboxyl groups. By having A2CO3 or AHCO3 present uniformly in the coating film, it is possible to improve hygroscopicity and evenly impart the function of releasing carbon dioxide when overcharged.

[0070] As described above, according to the present embodiment, by adding a filler and an alkali silicate to the coating liquid, it is possible to improve the electrical characteristics (output characteristics, cycle characteristics (lifetime)) of the battery while improving the mechanical strength and heat resistance of the porous film (separator).

[0071] Examples of the coating liquid, the porous film (separator) and the battery using the same according to the present embodiment will be described below.

[0072] [Example A] 1: Preparation of the substrate (porous film before coating) As the substrate S, for example, a commercially available polyethylene microporous membrane (manufactured by CS TECH, average pore size 0.06, thickness 16 μm) was used.

[0073] 2: Coating fluid preparation process A) Preparation of water glass As described above, water glass is an aqueous solution of an alkali silicate, and in this example, sodium silicate (Na2O·3SiO2 (ADEKA, ESX-2)) was used.

[0074] B) Adjustment of SA-CeNF Following the process in Figure 4, cellulose was hydrophobized with succinic anhydride (some of the -OH groups were converted to -COOH groups). Next, the hydrophobized cellulose in the dispersion was defibrated to nanosize the cellulose.

[0075] C) Mixing process Carboxymethylcellulose (CMC), acrylic resin (binder), and octylphenol ethoxylate (Triton X) as a surfactant were added to the dispersion of SA-CeNF, and then high-purity alumina (Sumitomo Chemical, average particle size 700 nm) was added. An aqueous solvent was further added as a solvent to adjust the mixture. This mixture was stirred at 2000 rpm for 30 min with a planetary centrifugal mixer (Thinky, ARE310), and finally water glass (sodium silicate) was added and stirred at 25 m / s for 1 min with a thin film gyratory mixer (Primix, FILMIX) to obtain a coating liquid. In the coating liquid, the ratio of solid components (cellulose, CMC, binder, surfactant, alumina, water glass (sodium silicate)) is set to 100 wt%, and the solid component ratio of each coating liquid is shown in Table 1. The surfactant was added in a solution with a solid content of 10 wt% so as to achieve the above ratio. In addition, as Comparative Example A, a coating liquid (simulating a commercial product) was also prepared to which no water glass (sodium silicate) or SA-CeNF dispersion was added.

[0076] [Table 1] In this embodiment, the ratio (concentration) of solid components (cellulose, CMC, binder, surfactant, alumina, water glass) to the solvent is 40 wt%, and this ratio (concentration) can be adjusted to approximately 25 wt% to 50 wt%.

[0077] 3: Coating process onto the substrate (separator manufacturing process) The substrate (PE porous film) described in "1. Preparation process of substrate (porous film before coating)" was cut into 50 mm squares to prepare substrate (test piece) S. The above-mentioned coating liquid (either coating liquid 1, 2, or A) was applied to both sides of the surface of this substrate S using a bar coater BC, and the coated film was dried for about 5 minutes with cold air from a dryer (Figure 6). Figure 6 is a perspective view showing the coating process of the coating liquid using a bar coater. The coating liquid was similarly applied to the back side. D is the groove depth of the bar coater BC, and the coating direction is the MD direction.

[0078] In this manner, porous films (separators) 1, 2, and A each having a coating layer formed thereon were formed (see Table 1). As Comparative Example B, a battery B described below was produced using a porous film (separator) that was only a substrate without a coating layer formed thereon.

[0079] The above-mentioned coating liquids 1, 2, and A and porous films (separators) 1, 2, and A were evaluated as follows.

[0080] 4: Evaluation of coating fluid and separator (Applicability) In Coating Solutions 1 and 2, there were no defects such as lumps or repellency from the substrate, and the coating properties were good.

[0081] (Gurley value) The time required for 100 ml of air to pass through was measured for the porous films (separators) 1, 2, and A, and this was taken as the Gurley value. The Gurley value was calculated by taking the average value of the N number (number of test pieces) of 5.

[0082] (Heat shrinkage test 1) The porous films (separators) 1 and A were left in a vacuum dryer at 180 to 220°C for 1 to 72 hours. The state of the film was observed before and after the application of a thermal load. The thermal shrinkage rate was calculated from the dimensional change of the film before and after the application of a thermal load. Since the substrate (PE porous film) used for coating was a dry separator manufactured by uniaxial stretching, the thermal shrinkage rate was calculated based on the dimensional change in the machine direction (MD). The thermal shrinkage rate was set to 100% when the film was melted and the dimensions could not be measured.

[0083] (Heat shrinkage test 2) The porous film (separator) 2 and A were left in a vacuum dryer at 300°C for 1 hour. The state of the film was observed before and after the application of a thermal load. The thermal shrinkage rate was calculated from the dimensional change of the film before and after the application of a thermal load. Since the substrate (PE porous film) used for coating was a dry separator manufactured by uniaxial stretching, the thermal shrinkage rate was calculated based on the dimensional change in the machine direction (MD). In addition, the thermal shrinkage rate was set to 100% when the film melted and the dimensions could not be measured.

[0084] (SEM observation) The surfaces of the above porous films (separators) 1, 2, and A were observed by SEM (scanning electron microscope).

[0085] (Puncture test) The porous films (separators) 1, 2, and A were fixed in a jig, and a needle having a diameter of 1 mm was pierced at a test speed of 10 mm / min, and the maximum force (N) until the needle penetrated was measured.

[0086] 5: Making the battery For the positive electrode slurry, positive electrode active material (NCM (lithium nickel cobalt manganese oxide, lithium nickel-cobalt-manganese oxide (Li(Ni 0.6 Co 0.2 Mn 0.2)O2)), conductive agent (acetylene black), and binder (polyvinylidene fluoride (PVdF)) were mixed in a solid ratio of 94:3:3 wt%, and kneaded using a planetary mixer (Thinky, Awatori Rentaro, 2000 rpm, 15 minutes) to form a slurry. This slurry was applied to a current collector (aluminum foil with a thickness of 15 μm) using an applicator, temporarily dried at 80°C, rolled with a roll press, and dried under reduced pressure (160°C, 10 hours) to form a positive electrode (positive electrode mixture layer). The capacity density was 3.10 mAh / cm 2 It was decided.

[0087] For the negative electrode slurry, the negative electrode active material (artificial graphite), conductive agent (acetylene black), thickener (carboxymethyl cellulose (CMC)), and binder (SBR (styrene butadiene rubber)) were mixed in a solid ratio of 96:1:1:2 wt%, and kneaded using a planetary mixer (Thinky, Awatori Rentaro, 2000 rpm, 15 minutes) to form a slurry. This slurry was applied to a current collector (copper foil with a thickness of 10 μm) using an applicator, temporarily dried at 80 ° C, rolled with a roll press, and dried under reduced pressure (140 ° C, 10 hours) to form a negative electrode (negative electrode mixture layer). The capacity density was 3.36 mAh / cm 2 It was decided.

[0088] Using the porous films (separators) 1, 2, and A, the positive electrode, and the negative electrode, R2032 coin-type batteries (batteries 1, 2, and A) were fabricated (see FIG. 3). 1 mol / L LiPF6 (EC:DEC=50:50 vol%, +VC1 wt%) was used as the electrolyte.

[0089] The above batteries 1, 2, A, and B were evaluated as follows.

[0090] 6: Battery evaluation (Cycle characteristics) The cycle characteristics of the coin-type batteries (batteries 1, 2, and A) were examined by repeatedly charging and discharging at 0.5 C after 10 cycles at a current of 0.1 C under conditions of 30°C and a cut-off voltage of 4.2 to 2.5 V. The cycle characteristics were also examined under conditions of 60°C.

[0091] (Battery resistance) The battery was charged at a current of 0.1 C for 10 cycles under conditions of 30°C and a cut-off voltage of 4.2 to 2.5 V, and then discharged at a specified rate (high-rate charge / discharge test). The battery was then discharged at a specified current value for 10 seconds, and the battery resistance was calculated from the relationship between the battery voltage and current value after 10 seconds.

[0092] 7:Result 7 to 10 are diagrams showing the results of heat shrinkage test 1. In each diagram, the upper part is a photograph showing the appearance of separator A and separator 1, and the lower part is a copy of the external shapes of separator A and separator 1. Fig. 7 shows the change after 1 hour at room temperature, Fig. 8 shows the change after 1 hour at 180°C, Fig. 9 shows the change after 3 hours at 200°C, and Fig. 10 shows the change after 72 hours at 220°C.

[0093] 11 is a diagram showing the results of heat shrinkage test 2. Here, the appearance of separator A and separator 2 are shown.

[0094] As shown in Figures 7 to 10, separator A, which uses coating solution A simulating a commercially available product, was found to have low heat resistance because the film completely melted after only one hour of heat load at 180°C (Figure 8). In contrast, separator 1, which uses coating solution 1 containing added water glass and cellulose, was found to have high heat resistance, with a thermal shrinkage rate of 0.5% after 72 hours of heat load at 220°C (Figure 10).

[0095] 11, the separator 2 using the coating solution 2 containing water glass and no cellulose had a heat shrinkage of 0.5% after a heat load of 300°C for 1 hour, proving that the separator A had high heat resistance. Note that the separator A was completely melted at 180°C and could not be measured.

[0096] 12 to 17 are diagrams showing the results of SEM observation: Fig. 12 and Fig. 13 show SEM photographs of separator A, Fig. 14 and Fig. 15 show SEM photographs of separator 2, and Fig. 16 and Fig. 17 show SEM photographs of separator 1.

[0097] 12 to 17, and particularly 13, 15, and 17, it can be seen that for separator A (FIG. 13), which uses coating liquid A simulating a commercially available product, alumina particles are relatively uniformly observed over the entire surface, whereas for separators 1 and 2 (FIGS. 15 and 17), which use coating liquids 1 and 2 to which water glass has been added, agglomeration of alumina particles is observed. The particle size of the aggregated particles is about 1 to 5 μm. Note that for separator 1, which uses coating liquid 1, the state of cellulose could not be confirmed by SEM observation.

[0098] FIG. 18 is a graph showing the results of the puncture test of the porous films (separators) 1, 2, and A, and FIG. 19 is a graph showing the Gurley values ​​of the porous films (separators) 1, 2, and A.

[0099] As shown in FIG. 18, the strength of the porous films (separators) 1 and 2 was found to be high and problem-free compared to separator A using coating liquid A simulating a commercially available product. In other words, it was found that there was no problem with the strength even if water glass or the like was added to the coating liquid. In addition, as shown in FIG. 19, the Gurley value was found to increase by less than 2% compared to separator A using coating liquid A simulating a commercially available product, and there was no problem. In other words, it was found that the gaps (micropores) between the substrate and alumina particles were not blocked and breathability was maintained even if water glass or the like was added to the coating liquid. It was also found that the Gurley value was improved by adding SA-CeNF.

[0100] Fig. 20 is a graph showing cycle characteristics at 30° C., and Fig. 21 is a graph showing cycle characteristics at 60° C. In Figs. 20 and 21, the horizontal axis represents the number of cycles (cycles), and the vertical axis represents the battery capacity retention rate (%).

[0101] 20 and 21, Battery 1 exhibited a better battery capacity retention rate than Battery A (Comparative Example A, commercially available coating liquid simulation). Battery 2 also exhibited a better battery capacity retention rate than Battery A (Comparative Example A, commercially available coating liquid simulation) in cycle characteristics at 60°C.

[0102] In comparing Battery 1 and Battery 2, it was found that Battery 1 had a better battery capacity maintenance rate.

[0103] Fig. 22 is a diagram (graph) showing the battery resistances of batteries 1, 2, A, and B. In Fig. 22, the vertical axis represents the DC resistance (Ω) of the battery. As shown in Fig. 22, the battery resistances of batteries 1 and 2 are higher than that of battery B, which uses a porous film (separator) that is only a substrate without a coating layer, but the rate of increase is within 10%, and it was found that the battery resistance is within an allowable range even when water glass or the like is added to the coating liquid.

[0104] The causes of this increase in battery resistance include factor 1) the addition of water glass, etc., blocks the micropores in the separator, inhibiting the movement of Li ions, and factor 2) components in the coating liquid dissolve into the electrolyte, preventing contact between the electrodes and the electrolyte, thereby reducing the effective electrode area.However, for batteries 1 and 2, the increase in battery resistance was slight, and it is believed that problems such as factors 1) and 2) above do not occur.

[0105] By using the above-mentioned Coating Liquids 1 and 2 as the coating liquid for the separator in this manner, it is possible to improve battery characteristics such as heat resistance and cycle characteristics.

[0106] (Embodiment 2) In the first embodiment, SA Ce is used as the second filler of the coating liquid, but oxidized cellulose having a structure in which a primary hydroxyl group is oxidized to a carboxyl group, such as TEMPO oxidized cellulose, may also be used. The following describes TEMPO oxidized cellulose as an example.

[0107] The porous film of the present embodiment and the method for producing the same will be described below. The porous film of the present embodiment can be used as a so-called battery separator.

[0108] [Structure description] The porous film of the present embodiment has a substrate (porous substrate) S and a coating film (coating film) CF formed on the surface of the substrate S. Here, the configuration of the porous film of the present embodiment (FIG. 1) and the configuration of the lithium ion battery using this porous film (FIGS. 2 and 3) are the same as those of the first embodiment except that SA-Ce in the first embodiment is replaced with TEMPO-oxidized cellulose, and therefore detailed description thereof will be omitted.

[0109] [Production method description] The manufacturing process of the porous film of this embodiment will be described below, and the configurations of the porous film and the coating film will be made clearer.

[0110] The manufacturing process of the porous film of the present embodiment includes the following steps.

[0111] <<1: Preparation process of the substrate (porous film before coating)>> The substrate S can be any substrate without particular limitation, and is preferably a substrate typically used for a porous film for a lithium ion battery, and may be a microporous membrane. For example, a commercially available polyethylene microporous membrane may be used.

[0112] <<2: Coating fluid preparation process>> 2-1) Preparation of the first filler In the present embodiment, inorganic particles (inorganic filler) are used as the first filler.

[0113] The inorganic particles are not particularly limited, and may be, for example, alumina, boehmite, aluminum hydroxide, nanosilica, microsilica, carbon nanotubes, talc, glass fiber, or the like, which are similar to those described in the first embodiment.

[0114] 2-2) Preparation of the second filler In this embodiment, TEMPO-treated cellulose is used as the second filler. TEMPO treatment (TEMPO oxidation treatment) is a treatment by oxidation reaction using TEMPO (2,2,6,6-tetramethylpiperidine1-oxyl) as a catalyst. For this reason, TEMPO-treated cellulose is sometimes called "TEMPO-oxidized cellulose."

[0115] Cellulose (Cellulose, Cell-OH) is (C 12 H 20 O 10 )n, for example, as shown in the above chemical structural formula (Chemical Formula 1).

[0116] When cellulose is treated with TEMPO, the primary hydroxyl group -OH of cellulose is regioselectively oxidized to a C6 aldehyde group and then to a C6 carboxyl group. This is then converted to a salt of the C6 carboxyl group (carboxylate) by alkali treatment. For example, when treated with sodium hydroxide solution, it is converted to the Na salt of the C6 carboxyl group as shown below.

[0117] [ka] In the step of introducing carboxyl groups to the hydroxyl groups of cellulose (oxidation step), for example, TEMPO or sodium bromide is used as a catalyst, and hypochlorous acid is used as an oxidizing agent to carry out the reaction in water. During the reaction, a basic solution capable of maintaining a desired pH, for example, sodium hydroxide, is added to carry out the reaction, thereby obtaining cellulose that has been subjected to a TEMPO oxidation treatment (above (Chemical formula 5)).

[0118] In this way, in TEMPO-treated cellulose (TEMPO-oxidized cellulose, TCe), the Na salt of the C6-carboxyl group is ionized in water, so that repulsion (electrostatic repulsion, osmotic pressure) works. Therefore, if the Na salt is arranged at a high density, it can be dispersed in a fine state. In the above chemical structural formula, only the left side of the two glucose residues is shown as a COONa group for the substituent of the carbon atom at the C6 position. This is an example that shows that it has a structure in which a part is oxidized to a carboxyl group, and does not mean that it is composed only of this structural unit. In other words, in the above chemical structural formula, it includes a case where both glucose residues have a structure in which the primary hydroxyl group is oxidized to a carboxyl group, and a case where both glucose residues do not have a structure in which the primary hydroxyl group is oxidized to a carboxyl group. As a whole, the oxidized cellulose only needs to have a structure in which a part of the primary hydroxyl group is oxidized to a carboxyl group. Furthermore, it is not necessary that all of the carboxyl groups are Na salts, and it also includes a case where a part of them is Na salt.

[0119] (Defibrillation process) The TEMPO-oxidized cellulose may be subjected to a defibration process to reduce the size of the cellulose (to a nano size). The defibration process (refining process) may be a chemical process or a mechanical process. A combination of these processes may also be used. By this defibration process (refining process), the cellulose becomes fine cellulose in a liquid, for example, with a width (minor axis, shorter length) W of 1000 nm or less and a length L of 500 μm or less, more preferably a width W of 500 nm or less and a length L of 3 μm or less. Note that cellulose with a width W of about 4 nm and a length L of about 2 μm has also been confirmed.

[0120] The above-mentioned pulverization (nanofiberization) of cellulose may be carried out before or after the TEMPO oxidation treatment.

[0121] 2-3) Preparation of alkali silicate As in the first embodiment, it is preferable to use water glass as the alkali silicate.

[0122] 2-4) Preparation of other additives Other additives that can be used, as in the first embodiment, include thickeners (e.g., carboxymethylcellulose, xanthan gum, guar gum, alginic acid), binders (e.g., acrylic resin, acrylic binder, fluororesin), dispersants (e.g., surfactants, alcohols), etc.

[0123] B) Mixing process (stirring process) A coating liquid is prepared by adding inorganic particles (first filler) and other additives to the above-mentioned dispersion of TEMPO oxidized cellulose (second filler), further adding an alkali silicate, and stirring.

[0124] The TEMPO oxidized cellulose (second filler) is preferably added in an amount of 0.05 wt% or more relative to the inorganic particles (first filler). The amount of the TEMPO oxidized cellulose is preferably 0.3 wt% or more and 8 wt% or less, more preferably 0.5 wt% or more and 5 wt% or less, relative to the total amount of solid components in the coating liquid.

[0125] The alkali silicate is preferably added in an amount of 0.05 wt% or more relative to the inorganic particles (first filler), and is preferably added in an amount of 0.3 wt% to 12.5 wt% or less, more preferably 0.5 wt% to 10 wt% or less, relative to the total amount of solid components in the coating liquid.

[0126] Examples of the stirring method that can be used include a method of rotating a blade attached to a shaft using a motor or the like, a vibration method using ultrasonic waves, etc. In order to reduce the entrapment of air bubbles in the coating liquid, the preparation (mixing and stirring) of the coating liquid may be performed under reduced pressure.

[0127] <<3: Coating process onto substrate>> The coating liquid is applied to the surface of the substrate S described in <<1: Preparation step of substrate (porous film before coating)>>. There is no limitation on the coating method, but for example, a bar coater, lip coater, gravure coater, die coater, spray coater, screen coater, etc. can be used. After coating, the coating liquid is dried to form a coating film on the surface of the substrate S.

[0128] The drying of the coating liquid is not particularly limited as long as the method can remove the solvent or dispersion medium contained in the coating liquid, and for example, a method of performing heat treatment at a temperature of 50°C or higher and 250°C or lower can be mentioned. The above heat treatment can be performed by holding for 0.1 to 50 hours. The drying environment can be exemplified by air atmosphere, vacuum atmosphere, rare gas atmosphere, nitrogen atmosphere, carbon dioxide atmosphere, and hydrogen atmosphere, and when the environment contains carbon dioxide, the alkali silicate reacts with carbon dioxide to generate a carbonate compound (A2CO3) or a hydrogen carbonate compound (AHCO3) (A = at least one element selected from Li, K, Rb, Ba, Ca, Mg, and Sr). Therefore, when the environment contains carbon dioxide, the alkali silicate contained in the coating film can contain a carbonate compound (A2CO3) or a hydrogen carbonate compound (AHCO3) (A = at least one element selected from Li, K, Rb, Ba, Ca, Mg, and Sr).

[0129] A2CO3 or AHCO3 has the characteristic that it has low solubility in water and decomposes to release carbon dioxide at a voltage exceeding 4.6 V. In other words, by including A2CO3 or AHCO3 in the coating film, the coating film becomes less likely to absorb moisture and can be endowed with the function of releasing carbon dioxide when overcharged.

[0130] The content of A2CO3 or AHCO3 in the coating film is preferably 1 wt% or more and 50 wt% or less. To adjust the content within this range, depending on the heat treatment temperature and heat treatment time, the environmental pressure should be 0.001 to 100 MPa absolute pressure and the carbon dioxide concentration should be 400 ppm or more. More preferably, the environmental pressure is 0.01 to 50 MPa, the carbon dioxide concentration is 1000 ppm or more, and even more preferably, the environmental pressure is 0.1 to 10 MPa, and the carbon dioxide concentration is 2000 ppm or more.

[0131] In addition, by using an alkali silicate in which A2CO3 or AHCO3 powder has been mixed in advance in the coating liquid, the process of heat treatment in an environment containing carbon dioxide can be eliminated, but it is preferable to have the alkali silicate absorb carbon dioxide to generate A2CO3 or AHCO3, because this can greatly reduce the hygroscopicity of the coating film. If the coating film is highly hygroscopic, it may absorb moisture from the air and degrade the battery characteristics.

[0132] When the coating solution contains cellulose as a second filler, A2CO3 or AHCO3 can be generated uniformly. In particular, the uniformity is improved when the hydrophilic group is replaced with a hydrophobic group or when the coating is treated with TEMPO. By having A2CO3 or AHCO3 present uniformly in the coating film, it is possible to improve the hygroscopicity and evenly impart the function of releasing carbon dioxide when overcharged.

[0133] As described above, according to the present embodiment, by adding a filler and an alkali silicate to the coating liquid, it is possible to improve the electrical characteristics (output characteristics, cycle characteristics (lifetime)) of the battery while improving the mechanical strength and heat resistance of the porous film (separator).

[0134] Examples of the coating liquid, the porous film (separator) and the battery using the same according to the present embodiment will be described below.

[0135] [Example B] 1: Preparation of the substrate (porous film before coating) As the substrate S, for example, a commercially available polyethylene microporous film (manufactured by CS TECH, average pore size 0.06 μm, thickness 16 μm) was used.

[0136] 2: Coating fluid preparation process A) Preparation of water glass As described above, water glass is an aqueous solution of an alkali silicate, and in this example, Na2O·3SiO2 (ADEKA, ESX-2) was used.

[0137] B) Preparation of TEMPO-oxidized cellulose TEMPO oxidized cellulose (Na salt) was prepared. This TEMPO oxidized cellulose was in powder form with an average particle size of about 10 μm, and was produced using pulp derived from broadleaf trees as the raw material.

[0138] C) Mixing process Carboxymethylcellulose (CMC), acrylic resin (binder), and octylphenol ethoxylate (Triton X) as a surfactant were added to the dispersion of TEMPO-oxidized cellulose, and then high-purity alumina (Sumitomo Chemical Co., Ltd., average particle size 670 nm) was added. An aqueous solvent was further added as a solvent to prepare a mixture. This mixture was stirred at 2000 rpm for 30 min with a planetary centrifugal mixer (Thinky Corporation, ARE310), and finally water glass (sodium silicate) was added, and the mixture was stirred at 25 m / s for 1 min with a thin film gyratory mixer (Primix Corporation, FILMIX) to obtain a coating liquid. In the coating liquid, the ratio of solid components (cellulose, CMC, binder, surfactant, alumina, water glass (sodium silicate)) is set to 100 wt%, and the solid component ratio of each coating liquid is shown in Table 2. The surfactant was added in a solution with a solid content of 10 wt% so as to achieve the above ratio. As Comparative Example A, a coating liquid (simulating a commercial product) was also prepared to which no dispersion of water glass (sodium silicate) or TEMPO-oxidized cellulose was added.

[0139] [Table 2] In this embodiment, the ratio (concentration) of solid components (cellulose, CMC, binder, surfactant, alumina, water glass) to the solvent is 45 wt%, and this ratio (concentration) can be adjusted to approximately 20 wt% to 60 wt%.

[0140] 3: Coating process onto the substrate (separator manufacturing process) The above coating liquid (any of coating liquids 3, 4, 5, 6, 7, and 8) was applied to both sides of the surface of the substrate (porous film made of PE) described in "1. Preparation process of substrate (porous film before coating)" using a bar coater, and dried at 80°C for 1 hour. The coating thickness was 4 μm on one side (8 μm on both sides). In this way, porous films (separators) 3, 4, 5, 6, 7, and 8 on which coating layers were formed were formed (see Table 2).

[0141] 4: Evaluation of coating fluid and separator (Applicability) For coating liquid 4, the coating liquid solidified and the bar coater became unable to move, so production of a porous film (separator) and a battery was abandoned. For coating liquids 7 and 8, the coating liquid did not wet and spread over the surface of the substrate (causing repelling), so production of a porous film (separator) and a battery was abandoned. For the other coating liquids, there were no problems such as solidification of the coating liquid or repelling of the substrate, and the coatability was good. Comparative Examples A and B are the same as those described in embodiment 1 (Example A).

[0142] (Heat shrinkage test 2) The porous film (separator) 3 was left in a vacuum dryer at 300°C for 1 hour. The state of the film was observed before and after the application of heat load. Since the substrate (PE porous film) used for coating was a dry separator manufactured by uniaxial stretching, the heat shrinkage rate was calculated based on the dimensional change in the machine direction (MD). In addition, the heat shrinkage rate was set to 100% when the film melted and the dimensions could not be measured.

[0143] 5: Battery construction and evaluation Similarly to Example A of the first embodiment, batteries (batteries 3, 5, and 6) were produced, and the cycle characteristics and battery resistance were evaluated.

[0144] 6:Result Fig. 23 is a diagram showing the results of heat shrinkage test 2. As shown in Fig. 23, the separator 3 using coating solution 3 containing added water glass and TEMPO-oxidized cellulose had a heat shrinkage rate of 0.5%, proving high heat resistance. In addition, it was found that this separator 3 has heat resistance that compares favorably with that of the separator 1 in heat shrinkage test 2 described above.

[0145] Fig. 24 is a graph showing cycle characteristics at 30° C., and Fig. 25 is a graph showing cycle characteristics at 60° C. In Figs. 24 and 25, the horizontal axis represents the number of cycles (cycles), and the vertical axis represents the battery capacity retention rate (%).

[0146] 24 and 25, Battery 3 exhibited a better battery capacity retention rate than Battery A (Comparative Example A, simulating a commercially available coating liquid). Battery 3 also exhibited a better battery capacity retention rate than Battery 6, which did not contain water glass (FIG. 25).

[0147] Fig. 26 is a diagram (graph) showing the battery resistances of batteries 3 and B. In Fig. 26, the vertical axis represents the DC resistance (Ω) of the battery. As shown in Fig. 26, the battery resistance of battery 3 is higher than that of battery B, which uses a porous film (separator) that is only a substrate without a coating layer, but the increase rate is within 10%, and it was found that the battery resistance is within an allowable range even when water glass or the like is added to the coating liquid.

[0148] As mentioned above, the causes of this increase in battery resistance include factor 1) the addition of water glass, etc., blocks the micropores in the separator, inhibiting the movement of Li ions, and factor 2) components in the coating liquid dissolve into the electrolyte, preventing contact between the electrodes and the electrolyte, thereby reducing the effective electrode area.However, for batteries 1 and 2, the increase in battery resistance was slight, and it is believed that problems such as factors 1) and 2) above do not occur.

[0149] By using the above-mentioned coating liquid 3 as a coating liquid for a separator in this manner, battery characteristics such as heat resistance and cycle characteristics can be improved.

[0150] (summary) From the results of the above examples, the amount of water glass added must be less than 15.5 wt% of the total amount of solid components in the coating liquid or coating film from the viewpoint of coatability, and is more preferably 10.5 wt% or less. Also, from the viewpoint of coatability and cost, the amount of water glass added must be less than 19.4 wt% of the amount of inorganic particles in the coating liquid or coating film, and is more preferably 12.4 wt% or less. It is believed that this amount of water glass added does not change much depending on whether cellulose is added or not, and the type of cellulose added.

[0151] Moreover, from the above examples and other experimental results, it is more preferable that the amount of cellulose added is 0.1 wt % to 5 wt % based on the total amount of solid components in the coating liquid or coating film.

[0152] Moreover, from the above-mentioned Examples A and B, it is possible to suppress the thermal shrinkage rate to 5% or less, more preferably 3% or less, by using the above-mentioned coating liquid.

[0153] In addition, the addition of water glass improves the viscosity of the coating liquid, and the amount of CMC, which acts as a thickener, can be reduced, for example, to 3 wt% or less based on the total amount of solid components in the coating liquid or coating film. In particular, since CMC is water-soluble and contains Na ions, it is preferable to reduce the amount of CMC added in order to suppress the deterioration of battery performance.

[0154] (Embodiment 3) In the examples of the first and second embodiments, a commercially available polyethylene microporous film was used as the substrate S, and the polyethylene microporous film can be formed as follows.

[0155] 27 is a schematic diagram showing the configuration of a manufacturing apparatus according to this embodiment. In this embodiment, a separator manufacturing process using the manufacturing apparatus will be described.

[0156] For example, a plasticizer (liquid paraffin) and a polyolefin (e.g., polyethylene) are fed into the raw material supply section of the twin-screw kneading extruder (S1) in Fig. 27, and the plasticizer and the polyolefin are kneaded in the kneading section. The kneading conditions are, for example, 180°C, 12 minutes, and the rotation speed of the shaft is 100 rpm.

[0157] The kneaded material (molten resin) is transported from the discharge section to the T-die S2, and the molten resin is extruded from a slit of the T-die S2 while being cooled in the raw material cooling device S3, thereby forming a thin-film resin molded body.

[0158] Next, the thin-film resin molded body is stretched in the longitudinal direction by a first longitudinal stretching device S4, and further stretched in the transverse direction by a first transverse stretching device S5.

[0159] Next, the stretched thin film is immersed in an organic solvent (e.g., methylene chloride) in extraction tank S6. In the stretched thin film, the polyolefin (e.g., polyethylene) and the plasticizer (paraffin) are in a phase-separated state. Specifically, the plasticizer (paraffin) becomes nano-sized islands. This nano-sized plasticizer (paraffin) is removed (degreased) by the organic solvent (e.g., methylene chloride) in extraction tank S6. This allows a porous thin film to be formed.

[0160] Thereafter, the thin film is further stretched in the transverse direction in the second transverse stretching device S7, while being dried and heat-set, and the internal stress generated during stretching is alleviated. Next, the thin film conveyed from the second transverse stretching device S7 is wound up by a winding device S8.

[0161] In this manner, a porous thin film (substrate of the first embodiment) can be manufactured. Here, for example, a gravure coating device (S7') shown in FIG. 28 is installed between the second transverse stretching device S7 and the winding device S8. FIG. 28 is a cross-sectional view showing a schematic configuration of the gravure coating device. This gravure coating device has two gravure rolls R. This gravure roll R has, for example, a plurality of oblique recesses, and is arranged so that a part of the gravure roll R is immersed in the coating liquid CL, and by rotating the gravure roll R, the coating liquid CL is applied to the substrate S with the coating liquid held in the oblique recesses.

[0162] By using the coating liquid CL described in the embodiment 1 as this coating liquid CL, it is possible to form a coating film on both sides of the substrate. If necessary, a drying device for the coating liquid or the like can be appropriately incorporated.

[0163] In this manner, high performance separators can be efficiently manufactured using the apparatus shown in FIGS.

[0164] As described above, polyolefin (resin) and a plasticizer are melt-kneaded using a kneader, extruded into a sheet using an extruder, and then stretched using a press or stretching machine to form a membrane (thin film).

[0165] The polyolefin to be used is one that can be processed by normal extrusion, injection, inflation, blow molding, etc. For example, homopolymers, copolymers, multistage polymers, etc. of ethylene, propylene, 1-butene, 4-methyl-1-pentene, 1-hexene, 1-octene, etc. can be used as the polyolefin. In addition, polyolefins selected from the group of homopolymers, copolymers, and multistage polymers can be used alone or in combination. Representative examples of the polymers include low density polyethylene, linear low density polyethylene, medium density polyethylene, high density polyethylene, ultra-high molecular weight polyethylene, isotactic polypropylene, atactic polypropylene, ethylene-propylene random copolymer, polybutene, ethylene propylene rubber, etc.

[0166] In addition, it is preferable to use a resin mainly composed of polyethylene as the base material S, because of the required performance of high melting point and high strength. In addition, from the viewpoint of shutdown property, it is preferable that polyethylene accounts for 50 wt% or more of the resin component. In addition, when using an ultra-high molecular weight polyolefin having a molecular weight of 1 million or more, it is preferable that the amount of ultra-high molecular weight polyolefin is 50 parts by mass or less per 100 parts by mass of the kneaded material (resin and dispersion liquid), because it becomes difficult to knead uniformly if the amount exceeds 50 parts by mass.

[0167] The plasticizer is added to the thermoplastic resin to improve flexibility and weather resistance. Furthermore, in this embodiment, the plasticizer is removed in a degreasing step described later, so that holes can be provided in the resin molded body (film).

[0168] As the plasticizer, an organic solvent having a molecular weight of 100 to 1500 and a boiling point of 50°C to 300°C can be used. Specifically, one or a mixture of several types of linear or cyclic aliphatic hydrocarbons such as liquid paraffin, nonane, decane, decalin, paraxylene, undecane, and dodecane, mineral oil fractions having boiling points corresponding thereto, and phthalic acid esters such as dibutyl phthalate and dioctyl phthalate that are liquid at room temperature can be used. In addition, one or a mixture of several types of alcohols such as ethanol and methanol, nitrogen-based organic solvents such as NMP (N-methyl-2-pyrrolidone) and dimethylacetamide, ketones such as acetone and methyl ethyl ketone, and esters such as ethyl acetate and butyl acetate can be used.

[0169] In the film (thin film) obtained by stretching the sheet-like kneaded material described above, the polyolefin and the plasticizer are in a phase-separated state. Specifically, the plasticizer becomes nano-sized islands. By removing this nano-sized plasticizer in the organic solvent treatment process described below, the islands of plasticizer become holes, forming a porous thin film. The process of forming a separator in which a large number of fine holes are formed in the resin molded body by the plasticizer removal process is called the "wet method."

[0170] For example, the film (thin film) formed in the above-mentioned stretching step is immersed in an organic solvent, whereby the plasticizer in the film is extracted into the organic solvent and removed from the film (thin film).

[0171] As the organic solvent, methylene chloride, hexane, octane, cyclohexane, etc. can be used. Among them, it is preferable to use methylene chloride from the viewpoint of productivity.

[0172] Thereafter, the organic solvent on the surface of the film (thin film) is volatilized, and the film is heat-treated (heat-set) as necessary, whereby the substrate (microporous film) S can be obtained.

[0173] (Application example) In the above, the Na salt of the C6-carboxyl group shown in (Chemical formula 4) is exemplified, but other counter ions (X +The counter ion is preferably an alkali metal ion, for example, K + etc.

[0174] [ka] Furthermore, the raw material for cellulose may be derived from vegetable fibers such as pulp, or from animal fibers such as sea squirts.

[0175] (Embodiment 4) In the first and second embodiments, the second filler is used, but if the drying process is performed in an environment containing carbon dioxide, the second filler is not necessarily required.

[0176] The porous film of the present embodiment and the method for producing the same will be described below. The porous film of the present embodiment can be used as a so-called battery separator.

[0177] [Structure description] The porous film of this embodiment has a substrate (porous substrate) S and a coating film (coating film) CF formed on the surface of the substrate S. Here, the configuration of the porous film of this embodiment (FIG. 1) and the configuration of the lithium ion battery using this porous film (FIGS. 2 and 3) are the same as those of the first embodiment except that they do not contain SA-Ce as in the first embodiment, but contain A2CO3 or AHCO3 (A=Li, Na, K, Rb) instead, and therefore detailed description thereof will be omitted.

[0178] [Production method description] The manufacturing process of the porous film of this embodiment will be described below, and the configurations of the porous film and the coating film will be made clearer.

[0179] The manufacturing process of the porous film of the present embodiment includes the following steps.

[0180] <<1: Preparation process of the substrate (porous film before coating)>> The substrate S can be any substrate, and is preferably a substrate that is generally used for a porous film for a lithium ion battery, and may be a microporous film. For example, a commercially available microporous polyethylene film or a microporous polypropylene film may be used.

[0181] <<2: Coating fluid preparation process>> 2-1) Preparation of the first filler In the present embodiment, inorganic particles (inorganic filler) are used as the first filler.

[0182] The inorganic particles are not particularly limited, and may be, for example, alumina, boehmite, aluminum hydroxide, nanosilica, microsilica, carbon nanotubes, talc, glass fiber, or the like, which are similar to those described in the first embodiment.

[0183] 2-2) Preparation of the second filler In this embodiment, the second filler is not used.

[0184] 2-3) Preparation of alkali silicate As in the first embodiment, it is preferable to use water glass as the alkali silicate.

[0185] 2-4) Preparation of other additives Other additives that can be used, as in the first embodiment, include thickeners (e.g., carboxymethylcellulose, xanthan gum, guar gum, alginic acid), binders (e.g., acrylic resin, acrylic binder, fluororesin), dispersants (e.g., surfactants, alcohols), etc.

[0186] B) Mixing process (stirring process) The above-mentioned inorganic particles (first filler) and, if necessary, additives such as a surfactant and an acrylic binder are added, and further an alkali silicate is added and stirred to prepare a coating liquid.

[0187] The alkali silicate is preferably added in an amount of 0.05 wt% or more relative to the inorganic particles (first filler). The alkali silicate is preferably added in an amount of 0.3 wt% or more and 5 wt% or less, more preferably 0.5 wt% or more and 1.5 wt% or less, relative to the total amount of solid components in the coating liquid.

[0188] Examples of the stirring method that can be used include a method of rotating a blade attached to a shaft using a motor or the like, a vibration method using ultrasonic waves, etc. In order to reduce the entrapment of air bubbles in the coating liquid, the preparation (mixing and stirring) of the coating liquid may be performed under reduced pressure.

[0189] <<3: Coating process onto substrate>> The above-mentioned coating liquid is applied to the surface of the substrate S described in <<1: Preparation step of substrate (porous film before coating)>>. There is no limitation on the coating method, but for example, a bar coater, lip coater, gravure coater, die coater, spray coater, screen coater, etc. can be used. After coating, the coating liquid is dried in an environment containing carbon dioxide, whereby a coating film can be formed on the surface of the substrate S.

[0190] In this embodiment, since the second filler as in the first and second embodiments is not included, when the coating film CF is dried in an environment that does not include carbon dioxide, the coating film CF blocks the micropores of the substrate S, and the Gurley value (air permeability, [sec / 100cc]) of the substrate S (porous film, separator) on which the coating film CF is formed is likely to be 3500 or more, and the breathability is poor (for example, when dried in an argon environment, the Gurley value was 3504sec / 100cc). Therefore, it is necessary to set the drying environment to an environment that includes carbon dioxide. By drying in an environment that includes carbon dioxide, the alkali silicate reacts with carbon dioxide to produce a carbonate compound (A2CO3) or a hydrogen carbonate compound (AHCO3) (A=at least one element selected from Li, K, Rb, Ba, Ca, Mg, and Sr) and silica (SiO2). Due to the produced A2CO3 or AHCO3, and SiO2, the coating film CF is not formed so as to cover all of the fine pores of the substrate S, and the Gurley value (air permeability, [sec / 100cc]) of the substrate S (porous film, separator) on which the coating film CF is formed is 200 or more and 3000 or less, thereby ensuring air permeability.

[0191] As described above, according to the present embodiment, by drying in an environment containing carbon dioxide, and adding a first filler and an alkali silicate to the coating liquid without using a second filler, it is possible to improve the electrical characteristics (output characteristics, cycle characteristics (lifetime)) of the battery while improving the mechanical strength and heat resistance of the porous film (separator).

[0192] Examples of the coating liquid, the porous film (separator) and the battery using the same according to the present embodiment will be described below.

[0193] [Example C] 1: Preparation of the substrate (porous film before coating) As the substrate S, for example, a commercially available polyethylene microporous film (manufactured by CS TECH, average pore size 0.06 μm, thickness 16 μm) was used.

[0194] 2: Coating fluid preparation process A) Preparation of water glass As mentioned above, water glass is an aqueous solution of an alkali silicate. In this embodiment, a mixture of Li2O·3.5SiO2 (Nihon Kagaku Kogyo, lithium silicate 35) and Na2O·3SiO2 (ADEKA, ESX-2) in a solid mass ratio of 1:1 was used.

[0195] B) Mixing process After adding acrylic resin (binder) and octylphenol ethoxylate (Triton X) as a surfactant to the water in which carboxymethyl cellulose (CMC) was dissolved, high-purity alumina (Sumitomo Chemical Co., Ltd., average particle size 700 nm) was further added. An aqueous solvent was further added as a solvent to prepare a mixed liquid. This mixed liquid was stirred at 2000 rpm for 30 minutes with a planetary centrifugal mixer (Thinky Corporation, ARE310), and finally water glass (a mixed liquid of lithium silicate and sodium silicate) was added and stirred at 25 m / s for 1 minute with a thin film gyratory mixer (Primix Corporation, FILMIX) to obtain a coating liquid. In the coating liquid, the ratio of solid components (CMC, binder, surfactant, alumina, water glass (lithium silicate + sodium silicate)) was 100wt%, and CMC was 0.9wt%, binder was 3wt%, surfactant was 0.1wt%, alumina was 85wt%, and water glass (lithium silicate + sodium silicate) was 11wt%. Note that the surfactant was added in a solution with a solid content of 10wt% to achieve the above ratio.

[0196] In this embodiment, the ratio (concentration) of the solid components (CMC, binder, surfactant, alumina, water glass) to the solvent is 45 wt%, and this ratio (concentration) can be adjusted to about 15 to 65 wt%.

[0197] 3: Coating process onto the substrate (separator manufacturing process) The above coating liquid was applied to both sides of the surface of the substrate (porous film made of PE) described in "1. Preparation process of substrate (porous film before coating)" using a gravure roll, and dried at 80°C for 1 hour in a carbon dioxide atmosphere of 0.1 MPa. The coating thickness was 4 μm on one side (8 μm on both sides). In this way, a porous film (separator) with a coating layer formed thereon was formed.

[0198] 4: Evaluation of coating fluid and separator (Applicability) This coating solution had good coatability without any problems such as solidification of the coating solution or cissing of the substrate.

[0199] 5: Gurley value of separator The time it took for 100 ml of air to pass through the porous film (separator) was measured, and this was taken as the Gurley value. For the Gurley value, the number of test pieces (N) was set to 5, and the average value was calculated.

[0200] 6:Result The Gurley value was 289 sec / 100 cc, indicating that breathability was ensured.

[0201] (summary) From the results of the above examples, when the second filler is not used, the Gurley value can be set to 200 or more and 3000 or less by drying (heat treating) the separator in an environment containing carbon dioxide. This is thought to be because drying in an environment containing carbon dioxide causes the alkali silicate and carbon dioxide to react to produce A2CO3 or AHCO3 and SiO2. It is thought that due to the produced A2CO3 or AHCO3, and SiO2, the coating film CF is not formed to cover all of the micropores in the substrate S. Although the lithium ion battery is exemplified above, it may be a metal lithium battery, a lithium polymer battery, an air lithium ion battery, etc. Also, it may be used as a separator for a non-aqueous electrolyte secondary battery such as a sodium ion battery, a potassium ion battery, a calcium ion battery, a magnesium ion battery, or an aluminum ion battery. These batteries refer to a battery system in which the ion (carrier) responsible for electrical conduction is replaced from lithium to a cation such as sodium, calcium, magnesium, or aluminum.

[0202] The invention made by the inventor has been specifically described above based on the embodiment and examples. However, the present invention is not limited to the above embodiment or examples, and it goes without saying that various modifications can be made without departing from the gist of the invention. [Explanation of symbols]

[0203] 1 positive electrode 1M Positive electrode mixture layer 1S current collector 2 negative electrode 2M Negative electrode mixture layer 2S current collector 6 cans (battery cans) 7 Lid (battery cap) 8 Washers CF coating film CL Coating Fluid R Gravure Roll S base material S1 Twin Screw Extruder S2 Die S3 Fabric cooling device S4 First longitudinal stretching device S5 1st horizontal stretching device S6 extraction tank S7 2nd horizontal stretching device S7' Gravure Coating Machine S8 Winding device SP Separator

Claims

1. A coating liquid for a porous film of a separator of a non-aqueous electrolyte secondary battery, the coating liquid comprising an alkali silicate and a first filler, The first filler is made of inorganic particles, The alkali silicate is contained in an amount of 0.05% by weight or more relative to the inorganic particles, The second filler has a content of 0.05% by weight or more relative to the inorganic particles, The second filler is a cellulose filler in which an OH group is substituted with a COOH group.

2. The coating solution according to claim 1, The coating liquid for a porous film, wherein the inorganic particles are a material selected from nanosilica, microsilica, carbon nanotubes, talc, alumina, boehmite, aluminum hydroxide, and glass fibers.

3. The coating solution according to claim 2, A coating solution for a porous film, wherein the second filler is TEMPO oxidized cellulose as shown below. 【Chemistry 6】

4. The coating solution according to claim 1, A coating liquid for a porous film, wherein the second filler is 12.4% by weight or less relative to the inorganic particles.

5. A porous film for a separator of a non-aqueous electrolyte secondary battery, comprising a porous substrate and a coating film provided on a surface of the porous substrate, the coating film includes an alkali silicate and a first filler, The first filler is made of inorganic particles, The alkali silicate is contained in an amount of 0.05% by weight or more relative to the inorganic particles, The coating film contains a second filler in an amount of 0.05% by weight or more relative to the inorganic particles, A porous film, wherein the second filler is a cellulose filler in which an OH group is substituted with a COOH group.

6. The porous film according to claim 5, A porous film, wherein the inorganic particles are a material selected from nanosilica, carbon nanotubes, talc, alumina and glass fibers.

7. The porous film according to claim 6, A porous film, wherein the second filler is TEMPO oxidized cellulose, as shown below. 【Chemistry 7】

8. The porous film according to claim 6, The coating film is A 2 CO 3 or AHCO 3 A porous film comprising (A=Li, Na, K, Rb).

9. The porous film according to claim 8, The above A 2 CO 3 Or the AHCO 3 is 1% by weight or more and 50% by weight or less with respect to the coating film.

10. The porous film according to claim 5, A porous film, wherein the second filler is 12.4% by weight or less relative to the inorganic particles.

11. A lithium ion battery comprising a positive electrode, a negative electrode, a separator, and an electrolyte, A lithium ion battery having the porous film according to any one of claims 5 to 10 as the separator.

Citation Information

Patent Citations

  • Rechargeable lithium-ion batteries and the use of glass-based materials in rechargeable lithium-ion batteries

    JP2015502627A

  • Separator layered product and manufacturing method thereof, and lithium battery

    JP2016207272A

  • Production method of porous film, and porous film

    JP2020070323A

  • Coating film composition for battery electrodes or separators, battery electrode or separator provided with coating film obtained by using same, and battery provided with battery electrode or separator

    WO2014136813A1

  • Inorganic particles for nonaqueous electrolyte battery

    WO2018101474A1